Optimizing α-tricalcium phosphate bone cement composite formulations: The critical role of bioactive glass particle size - Demir, Öznur; Oselska, Estere; Bertins, Maris; Viksna, Arturs; Boccaccini, Aldo R.; Loca, Dagnija (Materials & Design, 2024)
Calcium phosphate cements (CPCs) have been extensively utilized as bone grafting material due to their inherent osteoconductive properties, although they often lacked sufficient biological performance for effective bone healing at the defect site. Incorporating mesoporous bioactive glass (MBG) into CPCs offers a solution by improving porosity, promoting degradation and increasing the available surface area. In the scope of this study, we integrated MBG into CPCs and assessed the impact of varying MBG particle sizes (<20 µm, <38 µm, <100 µm) on the setting characteristics, microstructure, mechanical strength, and preliminary cell response of CPCs. Investigations revealed that < 20 µm MBG particles significantly improved the setting characteristics and compressive strength of CPCs, while < 38 µm particles promoted degradation and ion release, facilitating apatite formation. MBG incorporation was found to promote microstructural homogeneity and facilitate apatite formation, with particle size directly affecting these outcomes. Biocompatibility assessments indicated no cytotoxic effects, supported by the favorable cellular responses (> 92 % viability compared to control group). These findings underscore the critical impact of MBG particle size on developing advanced CPCs for biomedical applications, guiding future design and optimization strategies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Bioactive glass; Bone cements; Bone regeneration; Calcium phosphate; Mesoporous; Particle size